Advances in the development and characterization of combustible cartridge cases and propellants: Preparation, performance, and future prospects - Wu Mengde; Xiao Zhenggang (Reviews on Advanced Materials Science)
This study presents a comprehensive analysis of combustible cartridge cases (CCCs) and propellants with a focus on their preparation methods, characterization techniques, and application in modern weaponry. As a transformative alternative to traditional metal-based cartridges, CCCs act as both containment and energy sources, effectively reducing the weight and cost of ammunition. Our study classifies CCCs into types like nitrocellulose-based, microporous, resin-based, and nano-nitrocellulose cartridges – each with unique benefits and challenges. The investigation highlights emerging composite coating technologies that enhance environmental resilience and storage performance. Advanced techniques, including scanning electron microscopy combined with energy dispersive spectrum, differential scanning calorimetry, thermogravimetric, and terahertz time-domain spectroscopy, are discussed in this work to thoroughly examine the structural and thermal properties of CCCs and propellants. Additionally, we analyze the internal ballistics of propellants, focusing on their geometric structure, combustion rate, ignition delay, and compositional modifications, which are crucial for optimizing ballistic performance. The study concludes with insights into the reaction mechanisms. It offers a perspective on future directions, stressing the importance of developing more environmentally friendly and stable CCCs and propellants to meet modern ecological and safety standards.